The Effect of Job Characteristic, Person-Job Fit, Organizational Commitment on Employee Performance (Study of East Java BPJS Employees) - Nurtjahjono, Gunawan Eko; Nimran, Umar; Musadieq, Muh. Al; Utami, Hamidah Nayati (JPAS (Journal of Public Administration Studies), 2020)
Employee performance is the key to the success of an organization. The top priority of organizational leaders is how to create employees as prime human resources, have good behavior in the workplace and perform well based on needs in the workplace and have an understanding of the values that exist and are applied in the organization. The purpose of this study is to analyze and determine the effect of job characteristics, person-job fit, organizational commitment to employee performance. The population in this study were employees in East Java Province BPJS Employment with a total of 238 as a research sample. The research method uses survey research by distributing questionnaires to respondents. While the analysis of research data using Warp-PLS. The results showed that (1). The effect of job characteristics on person-job fit is positive and significant, (2). The effect of job characteristics on organizational commitment is positive and significant (3). The effect of job characteristics on employee performance is positive and significant (4). The influence of person-job fit on employee performance is positive and significant (5). The effect of organizational commitment on employee performance is positive and significant.Â